The Spiritual Dimension of Imran Hosein's ‘Methodology for the Study of the Qur'an: The Relevance of Esoteric Approaches to Contemporary Tafsir - Misbakhudin, Misbakhudin; Trisnani, Asif; Sa’dullah, Sa’dullah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research is based on the need for an approach to Qur'anic interpretation that is able to answer the spiritual crisis of modern Muslims, amid the dominance of rational-textual interpretations that often ignore the esoteric dimension of revelation. This study aims to examine and evaluate Imran N. Hosein's tafsir methodology in Methodology for the Study of the Qur'an, which offers a paradigm for reading the Qur'an based on spiritual depth, spiritual intuition, and the integration of meaning systems. The method used in this research is library research with a content analysis approach to Hosein's works and other supporting literature. The results of the study show that Hosein emphasizes the importance of purity of soul, daily recitation, direct practice of verses, and the connection of verses in the cosmic structure as prerequisites for a complete understanding. He also rejects the atomistic interpretation approach and calls for the restoration of the authority of revelation as the main epistemic source in Islamic studies. This finding confirms that there are significant contributions related to Hosein's methodology in building a transformative, integrative and contextual Qur'anic interpretation, while challenging the dominant legalistic and secularistic paradigm in contemporary Qur'anic studies. Imran Hosein has presented a new method of understanding the Qur'an as a form of self-purification, moral commitment and openness to the inner light of revelation. His approach mediates between the spiritual traditions of classical Islam and the ethical-transformative needs of people in the modern era.